2009
DOI: 10.1897/ieam_2008-032.1
|View full text |Cite
|
Sign up to set email alerts
|

Geodata‐based probabilistic risk assessment and management of pesticides in germany: a conceptual framework

Abstract: The procedure for the risk assessment of pesticides in Germany is currently further developed from a deterministic to a geodata-based probabilistic risk assessment (GeoPRA) approach. As the initial step, the exposure assessment for spray drift in permanent crops, such as vineyards, fruit orchards, and hops, is considered. In our concept, geoinformation tools are used to predict distribution functions for exposure concentrations based mainly on spatial information regarding the neighbourhood of crops and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The scientists within UFoH see a strong need to strengthen basic environmental research by developing novel methods (Ahlers et al 2008;Schwarzenbach et al 2006;Schaffer et al 2008), extending the environmental data base in the various fields, and by developing probabilistic risk assessment models (Schulz et al 2009) to predict the fate and the effect of environmental pollutants at the ecosystem level. The analysis presented here is in high accordance to a recent initiative supported by over 40 Swedish scientists (Albin 2006).…”
Section: Need For a Comprehensive Scientific Approachmentioning
confidence: 99%
“…The scientists within UFoH see a strong need to strengthen basic environmental research by developing novel methods (Ahlers et al 2008;Schwarzenbach et al 2006;Schaffer et al 2008), extending the environmental data base in the various fields, and by developing probabilistic risk assessment models (Schulz et al 2009) to predict the fate and the effect of environmental pollutants at the ecosystem level. The analysis presented here is in high accordance to a recent initiative supported by over 40 Swedish scientists (Albin 2006).…”
Section: Need For a Comprehensive Scientific Approachmentioning
confidence: 99%
“…Wang et al 12 proposed an integrated AHP-DEA (data envelopment analysis) methodology for bridge risk assessment. Schulz et al 13 suggested the use of geodata-based probabilistic method to assess risks. Aven 17 proposed matrix method to risk management for culvert rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…The general need for an improved quantification of risk has been recognized on various occasions, e.g., in working groups of FOCUS Landscape and Mitigation (FOCUS 2007a(FOCUS , 2007b, the EUFRAM project (Hart 2006), projects of the German Environmental Protection Agency (UBA PRA and GeoRISK; Schulz et al 2009), and a project of the German Crop Protection Association (IVA; Schad et al 2007), as well as in specific risk assessments Hendley et al 2001;Travis and Hendley 2001;Wang and Rautmann 2008). With respect to the introduction of probabilistic approaches, the focus of recent projects was to some extent on ''the effect side'' of the risk equation, i.e., addressing variability and uncertainty in the toxicity of a substance, for example, due to experimental design or intra-and interspecies variability (EUFRAM; Hart 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because the variability of risk to different species is largely driven by spatial and temporal variability of environmental and agronomic conditions that affect the spatiotemporal distribution of exposure and susceptible populations (Verdonck 2003), the use of geoinformation has become a prominent tool in recently refined risk assessment approaches Padovani et al 2004;Schad et al 2007;Schulz et al 2009). With the work of the FOCUS Landscape and Mitigation group (FOCUS 2007a(FOCUS , 2007b, basic aspects of landscape-level study designs have been evaluated and recommendations have been made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation